2018
DOI: 10.1159/000492560
|View full text |Cite
|
Sign up to set email alerts
|

HepaRG-Progenitor Cell Derived Hepatocytes Cultured in Bioartificial Livers Are Protected from Healthy- and Acute Liver Failure-Plasma Induced Toxicity

Abstract: Background/Aims: For applicability of cell-based therapies aimed at the treatment of liver failure, such as bioartificial livers (BALs) and hepatocyte transplantation, it is essential that the applied hepatocytes tolerate exposure to the patient plasma. However, plasma from both healthy donors and acute liver failure (ALF) patients is detrimental to hepatocytes and hepatic cell lines, such as HepaRG. We aimed to elucidate the underlying mechanisms of plasma-induced toxicity against HepaRG cells in order to ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…It has previously been reported that HepaRG cells are capable of overcoming treatment-induced damage when allowed a “recovery period” of maintenance in standard culture medium following cessation of treatment. 55 SRC is a parameter which is highly influenced by mitochondrial homeostasis, and as a result can be influenced heavily by external stimuli. 56 It has previously been reported that an increase in mitochondrial biogenesis can lead to increased SRC.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that HepaRG cells are capable of overcoming treatment-induced damage when allowed a “recovery period” of maintenance in standard culture medium following cessation of treatment. 55 SRC is a parameter which is highly influenced by mitochondrial homeostasis, and as a result can be influenced heavily by external stimuli. 56 It has previously been reported that an increase in mitochondrial biogenesis can lead to increased SRC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, liver cells rapidly deteriorate in the presence of human plasma, which limits the therapeutic window of the BAL [30,31]. This negative effect can be reversed by an intermittent phase of recirculating culture medium through the bioreactor [32]. Another challenge that extracorporeal BALs face is the provision of in vivo like bile secretion [33].…”
Section: Concluding Remarks Clinically Applied Cell-based Alssmentioning
confidence: 99%